Tensile and failure behaviors of Cu/Nb nanolaminates: the effects of loading direction, layer thickness, and annealing. (November 2022) - Zhang, Yifan; Gigax, Jonathan G.; Nizolek, Thomas J.; Carpenter, John S.; Schneider, Matthew M.; Li, Nan; Capolungo, Laurent; McCabe, Rodney J.
Abstract: Nano metallic laminates (NMLs) exhibit exceptional strengths. The viability of NMLs as structural materials, however, is also conditioned on their ductility and work-hardenability under arbitrary loading scenarios. While most studies show that NMLs exhibit high strength and good deformability under compression or nano-indentation, NMLs show limited ductility under tension. Additionally, the tensile properties of NMLs upon loading perpendicular to layer interfaces have not been explored. To fully comprehend the anisotropic plastic response of NMLs and identify routes for performance improvements, we conduct mesoscale tension tests of Cu/Nb NMLs along the layer normal direction (ND), rolling direction (RD), and transverse direction (TD), and examine the effects of annealing on strength and ductility. As-rolled (AR) Cu/Nb NMLs show near zero ductility for ND tension and fail before yielding via intergranular cracks propagating in Nb layers. Interestingly, it is found that annealing at 800 °C significantly enhances the ductility, work hardenability, and fracture toughness with limited decreases to overall strength. Moreover, annealing reduces the intralayer dislocation density and induces grain and layer morphology changes that facilitate co-deformation of Cu and Nb layers resulting in enhanced ductility and work hardenability. Graphical abstract: Image, graphical abstract